Narrative Shifts: Race, Culture, and the Production of Screendance - White, Marcus R (The International Journal of Screendance, 2018)
Moving 24fps is a platform where teams of one professional dance maker and one filmmaker are paired to create work in a single weekend. These ‘creatives’ make work as a part of the touring Festival: It focuses exclusively on the production of screendance and is situated within various ‘partner cities’. This article is informed by a collection of both informal and open forum interviews with over 25 creatives about their experience inside the project. We were curious how screendance can be used as a tool to help shape and reimagine each cities narrative as it relates to identity politics and what it could reveal about a national discourse of race and culture within the production of screendance. For the purposes of this journal, individual dance shorts from the Moving 24fps Detroit project will be used as case studies to examine the creative process and to investigate representation, equity, and inclusion in screendance curation and production. Two questions that frame this entire paper: What considerations and choices do creatives make to center race and geo-politics within their city? How does the project create or promote equity in dance film curation?